Participative diagnosis for territorial planning of protected areas:: subsidies to the Taim Ecological Station management plan, Brazil - Eichenberger, Caio Cavalcanti Dutra; Tagliani, Paulo (Sustainability in Debate, 2017)
The Taim Ecological Station is a protected area located in the Southern portion of the coastal plain of the Rio Grande do Sul State, Brazil. The station includes areas of the municipalities of Rio Grande and Santa Vitória do Palmar, located between the Mirim Lagoon and the Atlantic Ocean. In spite of having been established 30 years ago, and of its internationally recognized role as an important wetland area devoted to the protection of endangered species, the Taim Ecological Station still lacks an effective management and land use plan. This is due to the complexity of the challenges involved, including cultural and productive patterns that are in conflict with the objectives of conservation. Such conflicting patterns evidenced the importance of the implementation of participatory diagnosis process. The participatory diagnosis was used as a mechanism to increase citizens’ awareness about the role of the protected area as well as the scientific community’s involvement with the environment. Results of the diagnosis, which were generated through a geographic information system analysis and interpreted in combination with physical, biological and anthropogenic data allowed to characterize territorial threats and opportunities within the conservation area of the unit. Results allowed the design of a land use zoning plan, as well as the identification of management actions to support land planning activities in the area.